Virtual pair programming and online oral exams: effects on social interaction, performance, and academic integrity in a remote computer programming course - Lubarda, M. V.; Phan, A. M.; Schurgers, C.; Delson, N.; Ghazinejad, M.; Baghdadchi, S.; Minnes, M.; Kim, M.; Pilegard, C.; Relaford-Doyle, J.; Sandoval, C. L.; Qi, H. (Computer science education, 2025)
Pair programming and oral exams were deployed in tandem in a remote undergraduate computer programming course to promote social interaction and enhance learning. We investigate their impact on social interactions, sense of connection, academic performance, and academic integrity within a virtual learning environment, and explore the dynamics of student collaboration in the context of voluntary pair programming. Students' coding activities, pairing preferences, and performance were survey responses were recorded and analyized. First and second year students were more likely to participate in virtual pair programming than their more senior classmates. Willingness to pair program strongly correlated with GPA. Partner changes were infrequent. 20-40% of students pair programmed per assignment. Oral exam scores positively correlated with other course scores. Surveys indicated that virtual pair programming and oral exams positively impacted learning, sense of community, and academic integrity. The study offers perspectives on how these practices can be leveraged to foster inclusive learning, meaningful discourse, peer collaboration, and student-faculty relationships, with a positive effect on student motivation and academic integrity.